Juvenile Central Retinal Artery Occlusion Associated With Atrial Septal Defect - Lyons, Lance J.; Yarrabolu, Tharak; Kuffel, Ronald R.; Bishop, John E. (Journal of pediatric ophthalmology and strabismus, 2019)
A 16-year-old boy presented with acute unilateral painless vision loss associated with a central retinal artery occlusion. Subsequent studies revealed an atrial septal defect of 17 mm, which was closed via a cardioform septal occluder. [J Pediatr Ophthalmol Strabismus. 2019;56:e73–e75.]